STUDY ON AVIPATTIKAR CHURNA AND KAPARDIKA BHASMA IN THE MANAGEMENT OF HYPERACIDITY (AMLAPITTA) - Mangal Anil,Jadhav A.D.; Reddy R. G. (International Journal of Applied Ayurved Research, 2016)
Hyperacidity (Amlapitta) simply means increase acid secretion in the stomach. Burning sensation in upper abdomen, burning sensation in chest, acid eructation, water brash, vomiting, nausea, vertigo, flatulence, constipation, and tenderness in upper abdomen are symptoms of this disease. To evaluate the efficacy of Avipattikar churna and Kapardika Bhasma a clinical study was conducted at R A Podar Central Research Institute Hospital, Mumbai on 33 patients of Amlapitta. Among 33 cases, 27 cases good responded, 5 fair responded and only one patient poor response. The Ayurvedic intervention was found very effective in the management of Amlapitta(p<0.0001). No any adverse effects were observed during and after the treatment.